2014
DOI: 10.1186/1471-2261-14-187
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use in patients with type 2 diabetes mellitus is associated with reduced risk of deep vein thrombosis: a non-randomized, pair-matched cohort study

Abstract: BackgroundMetformin, an insulin-sensitizer, may correct several physiologic abnormalities owing to insulin resistance in patients with type 2 diabetes mellitus (DM). The effects of metformin on venous thrombosis in patient with type 2 DM have not been reported. Our study strived to explore the relationship of metformin therapy and the subsequent development of deep vein thrombosis (DVT) using a nationwide, population-based database.MethodsFrom 1997 to 2003, we identified a study cohort consisting of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The studied comorbidities, diabetes, ischemic heart diseases and cancer, were not significantly associated with the occurrence of DVT among the participants in the current study. These findings are in line with what was reported by ( 16 , 18 , 23 , 24 ) where these comorbidities had no significant effect on DVT development in the studied population. Furthermore, another study conducted by ( 17 , 26 ) found that diabetes and ischemic heart diseases were not significantly associated with the occurrence of DVT.…”
Section: Discussionsupporting
confidence: 93%
“…The studied comorbidities, diabetes, ischemic heart diseases and cancer, were not significantly associated with the occurrence of DVT among the participants in the current study. These findings are in line with what was reported by ( 16 , 18 , 23 , 24 ) where these comorbidities had no significant effect on DVT development in the studied population. Furthermore, another study conducted by ( 17 , 26 ) found that diabetes and ischemic heart diseases were not significantly associated with the occurrence of DVT.…”
Section: Discussionsupporting
confidence: 93%
“…Literature reports have connected metformin with reduced mortality and diabetes-associated cardiovascular and cerebrovascular events in diabetic patients891011. However, it is not known whether metformin is effective against thrombosis in both diabetic and normal individuals, and further investigation is merited to determine its precise mechanism of action with respect to thrombosis prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is widely used as the first-line therapy for type-2 diabetic patients. It has been reported that metformin reduced mortality and diabetes-associated thrombotic complications89101112. However, its mechanism of action is largely unknown with respect to thrombosis prevention, and further investigation is merited.…”
mentioning
confidence: 99%
“…18 Metformin treatment is protective in experimental models of heart failure 19, 20 and is safe when used in diabetic patients with congestive heart. 20, 21 The mechanism of metformin protection is involved in activation of AMP-activated protein kinase (AMPK). AMPK is a cellular energy sensor that regulates mitochondrial metabolism and the redox state of the cell.…”
mentioning
confidence: 99%